Fraseología en los titulares de un tabloide - Solís Aroni, Nora (2019)
This study describes the phraseological units —collocations, locutions and directive formulas— used in the headlines of the newspaper El Trome, since this seems to be one of the main causes of the preference of its readers. The Corpas model was used for the description. As a result, it was found that in the headlines there is a greater use of collocations, followed by locutions. In addition, two new collocations with a more complex structure are proposed.